2007
DOI: 10.1111/j.1365-3016.2007.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing levels of contaminants in breast milk: methodological issues and a framework for future research

Abstract: To assess the scale of the possible exposure by the breast-fed infant to potentially harmful substances in breast milk, methodologically robust studies are essential. Many studies in this field, however, do not report details of crucial issues such as recruitment and milk sampling. The aims of the study reported here were to develop robust methods for the study of contaminants in breast milk, and to develop a framework for future research and population monitoring. Three cohorts of women and babies were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Some of the above studies have used this measure in attempts to better define maternal exposure whilst others are used to indicate risk of infant exposures. For lipophilic xenobiotics in general, the measuring and understanding of the kinetics and variations of those kinetics of the transfer from maternal exposure to breast milk samples are complex [70]. For aflatoxins a small survey from Gambia ( n = 5) over several days collection suggested that about 0.1–0.4% of the ingested AFB1 was transferred to milk [69].…”
Section: Mycotoxin Exposure Biomarkersmentioning
confidence: 99%
“…Some of the above studies have used this measure in attempts to better define maternal exposure whilst others are used to indicate risk of infant exposures. For lipophilic xenobiotics in general, the measuring and understanding of the kinetics and variations of those kinetics of the transfer from maternal exposure to breast milk samples are complex [70]. For aflatoxins a small survey from Gambia ( n = 5) over several days collection suggested that about 0.1–0.4% of the ingested AFB1 was transferred to milk [69].…”
Section: Mycotoxin Exposure Biomarkersmentioning
confidence: 99%
“…(6) Avoid breast manipulation, nipple redirection and rapid thrusting of the baby to the breast. (7) Increase research and improve knowledge about the possible effects of pharmaceutical and other substances transported to the unborn and breastfed baby 95 and, (8) avoid overt and covert use and promotion of non-human milk products for babies.…”
Section: Discussionmentioning
confidence: 99%
“…caffeine, nicotine, alcohol), and illegal drugs, can also all appear in maternal milk (). Measurement of these substances or their metabolites in breast milk is tempting, and considerable effort has recently been devoted to demonstrating the feasibility of collecting and storing samples in a general population 50 . One of the problems is that the composition of milk varies throughout a feed, with a far higher concentration of fat at the start compared with the end of a breast feed.…”
Section: Breast Milkmentioning
confidence: 99%
“…Another problem concerns the fact that some substances (such as phthalates) degrade rapidly, and storage even at −70°C will not prevent this. In the short term, however, biodegradation seems not to be such a problem and samples can even be sent through the post satisfactorily 50 …”
Section: Breast Milkmentioning
confidence: 99%